PLATFORM DEVELOPMENT FOR PHOTODETECTOR LINEARIZATION BY SOFTWARE METHOD USING CODE GENERATION FOR MICROCONTROLLERS OF DIFFERENT HARDWARE ARCHITECTURES - DOBROVOLSKY, YURIY; PROKHOROV, PAVLO; PAVLIUCHENKO, OLEH; MAKARUK, OLEG (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Article describes a software method for solving the problem of linearization of the output current of the photodetector outside the dynamic range using microcontrollers, provided that the solution can be deployed on different microcontroller architectures for a large number of different types of photodetectors, while any number of experimental measurements of their characteristics can be entered and processed for each of these photodetectors. Described approach offers platform development that can be deployed on separate computing capacities, the tasks of which will be to process a given number of measurement results taken from the empirical results of photodetector output current measurements, on the basis of which a mathematical model of the dependence of the output current values of the photometer from the input values of the optical signal will be evaluated, with further generation of the source code for any of the supported microcontroller architectures. The article also considers the specificity of development and evaluation of linearization function for photodetector, namely the approximation of the piecewise-determined function of output current value of the photodetector with linear and non-linear part, depending on the external power supplied by the light flux, as well as the definition of the boundary of these parts, also known as a knot. In addition, the implementation of algorithms and approaches to convert calculated mathematical models from a single high-level computing environment on a certain computing station into low-level software code are considered, include further loading and execution by the internal computing environment of a microcontroller of a certain architecture. The platform described in the article allows to facilitate the recording and processing of experimental data on the characteristics of photographic devices and can be implemented in research laboratories and/or production.
Keywords: photodetectors; dynamic range; microcontrollers; code generation; software engineering